The Relationship Between Generalized Anxiety Symptoms and Treatment Dropout Among Women in Residential Treatment for Substance Use Disorders. (6th June 2016) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott E.; Stuart, Gregory L.
ABSTRACT: Background : Generalized anxiety disorder (GAD) co-occurs with substance use disorders (SUDs) at an alarmingly high rate, and the presence of anxiety is associated with an increased risk for relapse to substance use following treatment. Furthermore, comorbid SUDs and other forms of psychopathology are associated with an increased risk for leaving treatment against medical advice (AMA). Objective and Method : Research has yet to examine whether the presence of GAD symptoms is associated with leaving treatment AMA in SUDs populations. Thus, the current study sought to address this important gap in the literature by examining this relationship among a sample of 122 women in residential treatment for SUDs. Results : Results demonstrated that GAD symptoms were significantly associated with the decision to leave treatment AMA after controlling for age, education, problematic alcohol and drug use, and depression symptoms. Conclusions/Importance : Our finding indicates the potential importance of assessing and targeting GAD in treatment for SUDs, which may increase treatment compliance.